Structural design of CNG storing composite pressure vessels for marine applications - Τσώνος, Άγγελος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Θαλάσσιων Κατασκευών. Εργαστήριο Ναυπηγικής Τεχνολογίας, 2017)
The use of the natural gas as a propulsion fuel is becoming gradually more popular in the marine industry, as it offers complete compliance with the recent emission restrictions (SOx and NOx). However, further research is needed for its onboard storage. CNG is stored in pressure vessels able to withstand operating pressures above 250bar. Although the use of composite materials for their construction offers a lightweight solution, it imposes new challenges to the structural designer. The use of simulation software packages, that utilize the Finite Element Method (FEM), is an efficient and economically feasible option to cope with the former issue. In the context of this thesis, a simulation model was developed in Abaqus software. The development of the model demanded extensive bibliographic research concerning designing and manufacturing aspects of composite pressure vessels. The research included important for the structural behavior of the pressure vessel topics like winding trajectories and modeling of thickness build-up at the dome regions. The design parameters and the extent at which they affect the aforementioned topics were also investigated. In addition, the theoretical modeling of the thickness build-up at the dome region was verified with thickness measurements at a constructed pressure vessel. The obtained theoretical knowledge was used in the development of the simulation model. This model was used for the conduction of a parametric study, which investigated the design parameters that affect the structural behavior of the pressure vessel and helped in the optimization of its weight. Finally, based on the conclusions of the parametric study, the structural design of a pressure vessel was made. The pressure vessel is designed to be used in marine applications.